Peranan Raja La Maddaremmeng Dalam Penyebaran Islam Di Bone - Nasruddin, Nasruddin (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
King Bone to Lamaddaremmeng XIII has a very large role and has the effect of early-early development of Islam in southern Sulawesi. He Maddaremeng is committed to enforce Sharia Law. His efforts were Eliminating slavery, Addition parewa Sara, to revamp the governance structure by adding positions previously unknown structure that positions parewa sara, eradication of idols, eliminating the arbitrary actions on others, Equal rights. Other efforts are trying to eliminate the differences in the degree of the community.